2019
DOI: 10.1370/afm.2390
|View full text |Cite
|
Sign up to set email alerts
|

Team-Based Clinic Redesign of Opioid Medication Management in Primary Care: Effect on Opioid Prescribing

Abstract: PURPOSE Six key elements of opioid medication management redesign in primary care have been previously identified. Here, we examine the effect of implementing these Six Building Blocks on opioid-prescribing practices. METHODS Six rural-serving organizations with 20 clinic locations received support for 15 months during the period October 2015 to May 2017 to implement the Six Building Blocks. Patients undergoing long-term opioid therapy (LtOT) at these study sites were compared with patients undergoing LtOT enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…29,30 At the same time, the call to action to address primary care clinician and staff burnout 31 points to the importance of implementing opioid quality improvement programs that focus not only on patient safety, but also on the work-life conditions of staff and clinicians. The Six Building Blocks program has found that in addition to significant declines in both the proportion of patients on high-dose opioids and the total number of patients receiving opioids in participating clinics, 19 implementing these system-based improvements to opioid medication management also improved clinician and staff perceptions of work-life quality. Future studies should assess the patient perspective specific to clinic redesign programs such as the Six Building Blocks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 At the same time, the call to action to address primary care clinician and staff burnout 31 points to the importance of implementing opioid quality improvement programs that focus not only on patient safety, but also on the work-life conditions of staff and clinicians. The Six Building Blocks program has found that in addition to significant declines in both the proportion of patients on high-dose opioids and the total number of patients receiving opioids in participating clinics, 19 implementing these system-based improvements to opioid medication management also improved clinician and staff perceptions of work-life quality. Future studies should assess the patient perspective specific to clinic redesign programs such as the Six Building Blocks.…”
Section: Resultsmentioning
confidence: 99%
“…18 A study team from the University of Washington and the MacColl Center for Health Care Innovation at the Kaiser Permanente Washington Health Research Institute tested implementation of the Six Building Blocks through a facilitated program. 19 This program included practice coaching, connection to resources, clinical education, and shared learning with other participating organizations and clinical advisors, described in more detail in Table 1. Following implementation, clinics saw a significant decrease in the number of patients using LtOT and the proportion of patients on high opioid doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects and setting have been previously described [14]. Briefly, six rural-serving primary care organizations with 20 clinic locations in the Washington, Wyoming, Alaska, Montana, and Idaho (WWAMI) region Practice Research Network were enrolled in the study.…”
Section: Intervention Setting and Subjectsmentioning
confidence: 99%
“…The Six Building Blocks program was subsequently implemented across 20 rural and rural-serving clinics within six organizations. Study outcomes have been previously published [14]. Briefly, the rate of decline in the total number of patients on LtOT increased during the Six Building Blocks' 15 months of practice facilitation support.…”
Section: Introductionmentioning
confidence: 99%